2010
DOI: 10.1016/j.intermet.2009.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Importance of the atom-pair bond in metallic alloying

Abstract: a b s t r a c tRajasekharan and Girgis reported that binary systems with intermetallic compounds of a particular crystal structure form a straight line on a map using Miedema's parameters. In this paper, the universality of that observation is examined. Observations from a study of 143 binary systems that crystallize in six different crystal structures at AB 3 composition are discussed. Prediction of concomitant and mutually exclusive structure types in binary metallic phase diagrams, and of phase transitions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 20 publications
1
28
0
Order By: Relevance
“…Hence, apart from the tremendous practical utility of the RG map, there is also the interesting question of why the map predicts structures. The answer to this question has been attempted by Rajasekharan and Seshubai elsewhere [12]. According to them, each point on the RG map stands for the energy of the nearest neighbor atom-pair bond in a binary system and this energy remains nearly the same at all compositions in the binary system.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Hence, apart from the tremendous practical utility of the RG map, there is also the interesting question of why the map predicts structures. The answer to this question has been attempted by Rajasekharan and Seshubai elsewhere [12]. According to them, each point on the RG map stands for the energy of the nearest neighbor atom-pair bond in a binary system and this energy remains nearly the same at all compositions in the binary system.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Corresponding to a binary system A-B, there can be two symmetrically opposite points on the ( , n wsA ) as the 'Inverse RG line' of the structure type [12]. We note that the composition at which a structure type occurs does not enter into deciding its coordinates on the RG map; thus each point on the map represents a binary system, and not a particular intermetallic compound.…”
Section: Construction Of Rajasekharan-girgis Mapmentioning
confidence: 99%
See 2 more Smart Citations
“…Rajasekharan and Girgis (RG) 5,6 had observed that binary systems with intermetallic compounds of the same crystal structure occur along a straight line on a (D/,DN 1/3 ) map, referred to hereafter as the RG map. Considering 96 structure types with ;3000 compounds, [7][8][9] it has been demonstrated that D/ } DN 1/3 with a slope ; þ ffiffiffiffiffiffiffiffiffi Q=P p for all the structure types. Binary systems with compounds of 88 of the structure types formed single straight lines and six of them formed dual lines, whereas AuCu 3 and NaCl structure types formed multiple lines.…”
Section: Introductionmentioning
confidence: 99%